Real-Time Speed Control of BLDC Motor Based On Fractional Sliding Mode Controller - Abdullah BAŞÇI; Kamil ORMAN; Kaan CAN; Adnan DERDIYOK (International Journal of Applied Methods in Electronics and Computers, 2016)
The design of the system used for brushless DC (BLDC) motor control in speed and position control is difficult due to the non-linear structure. Therefore, the designed controller is required to respond to these challenges and need high-efficiency operation. This paper presents the experimental validation of a robust speed control structure of a BLDC motor based on continuous sliding mode (CSM) and fractional-order sliding mode (FOSM) controllers. The controllers have been tested for low and medium speed reference signals and amplitude values. Then, both controllers have been compared in term of tracking performance and error elimination and the results have been shown graphically. Experimental results prove that the FOSM controller shows better trajectory tracking performance than CSM controller with high precision as well as good robustness against changes of references.